CORPORATE MEETING DESTINATION CHOICE: THE INFLUENCE OF CONSUMPTION VALUES IN THE MALAYSIAN PERSPECTIVE - M. ARIFFIN, AHMAD AZMI (ITB Journal Publisher, LPPM ITB, 2008)
This study attempted to determine the influence of consumption value on the novelty preference for corporate meeting destination choice. The theory of consumption value as proposed by Sheth et al. (1991) was employed as the internal motivating drive to explain the choice between conventional and novel meeting destinations. The consumption value theory by Sheth et al. (1991) was the best typology to be employed in this study because of its multidimensional properties composed of both objective value (functional) and perceptual values (epistemic, emotional, social and conditional) attributes. A total of 75 corporate meeting planners drawn from public listed services organizations were involved. The main method of data collection was questionnaire survey and multiple regression analysis was employed as the main statistical technique. The results revealed that functional value exerted a negative effect on novelty preference while epistemic value was positively related to novelty preference for corporate meetings.